Need help on an algebra problem?

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

Find the solution of 

(2/x-3) + (4/5x+1) = 11/5x^2-14x-3

Feb 15th, 2015

(2/x-3) + (4/5x+1) =[2(5x+1)+4(x-3)]/ (x-3)(5x+1)

                             =(10x+2+4x-12)/ (x-3)(5x+1)

                             =(14x-10)/ (x-3)(5x+1)

11/5x^2-14x-3=11/(5x+1)(x-3)

So (14x-10)/ (x-3)(5x+1)=11/(5x+1)(x-3)

                         14x-10=11

                              14x=21

                                  x=3/2


Feb 15th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Feb 15th, 2015
...
Feb 15th, 2015
Oct 24th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer